Receptions of Paul in early Christianity: the person of Paul and his writings through the eyes of his early interpreters - Schröter, Jens; Butticaz, Simon; Dettwiler, Andreas; Paul, Clarissa (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2018)
The volume deals with interpretations of Paul, his person and his letters, in various early Christian writings. Some of those, written in the name of Paul, became part of the New Testament, others are included among „Ancient Christian Apocrypha", still others belong to the collection called „The Apostolic Fathers". Impacts of Paul are also discernible in early collections of his letters which became an important part of the New Testament canon. This process, resulting in the „canonical Paul", is also considered in this collection.